Memajukan Ekonomi melalui Pemanfaatan Biogas dari Kotoran Sapi di Desa Makmur Sejahtera - Andi Irfan; Harkaneri Harkaneri; Rimet Rimet; Dessyka Febria (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The utilization of cow feces as an alternative energy source, namely biogas, is a substitute for fossil fuels for humans for environmental sustainability. The purpose of this service activity is to form an asset-based community that is driven by community or society. Methodology/approach: The service is located in Makmur Sejahtera Village, Gunung Sahilan District, Kampar Regency. The cattle breeder community in this village consisted of 31 heads of families with more than 150 cattle. The method chosen for this service activity was the ABCD method. Results/findings: The results of this community service show community awareness of the use of cow dung in biogas. The main aim is to improve the community's economy in addition to making an effort to save the environment sustainably. BUMDes Sejahtera Bersama, owned by Makmur Sejahtera, has not been able to manage biogas or become a container because it is feared that it will not be managed well, and that access is far from reactors that are already in production. Conclusion: Failures in reactors are discussed to find practical solutions that can be implemented immediately, namely, by looking for reactor leaks and waiting longer for biogas production. Limitation: This service only involves smaller community groups, and the amount of cow feces is reduced owing to the increasing demand for beef. Contribution: This community service is able to increase public awareness of the use of cow dung in biogas, and in the future, the village government is committed to developing the community to improve the community's economy.